The intellectual trajectory of Braj B. Kachru. Issue 1 (9th July 2019) - Sridhar, S.N.; Sridhar, Kamal K.
Abstract: Braj Kachru is a major figure in linguistics and English studies, and he has left us an intellectual legacy that speaks to a wide range of fields in language studies, including sociolinguistics, variation studies, bilingualism and multilingualism, applied linguistics, second language acquisition, and teaching English as a second or foreign language. This article sets out to provide a detailed and nuanced study of the intellectual trajectory of one of the most influential figures in contemporary sociolinguistics and English studies.